Risk Factors that Affect The Incidence of Dengue Haemorrhagic Fever in The Work Area of Puskesmas Pare - Ericha Fitria Widyatama (Universitas Airlangga, 2018)
Pare Community Health Center or Puskesmas is one of Puskesmas in Kecamatan Pare which has the highest number of Dengue Hemorrhagic Fever incidence that is 64 incidence in 2016. The purpose of this study is to analyze the risk factors that affect the incidence of Dengue Hemorrhagic Fever in the work area of Puskesmas Pare. It was an observational study with cross sectional approach. Interviews and environmental observations were conducted on 100 respondents, randomly, in the working area of Puskesmas Pare, Desa Tulungrejo. The independent variables of the research were larvae existence , maya index status and 4M Plus behavior, with the dependent variable of the research was Dengue Hemorrhagic Fever incidence in 2016.This data was analized by binary logistic regression test.The results of this study indicate that risk factors that affect the incidence of Dengue Hemorrhagic Fever is the action of 4M Plus (p = 0,017).Therefore, the 4M Plus actions should be further improved independently and promoted evenly to the community in order to suppress the incidence of Dengue Hemorrhagic Fever.